(3GdcJGHI GdYdGLjI ef GdGSJTaGA HGddZI Edi TaGA GddZI (B/s - (3MSjf, Ydj YHO GdefYes; (3aVd Gddg, eMeO QLHs ((3GdLjRI (B- [(3eUQ(B] :s (3OGQ GdQHi ddfTQ hGdJhRjY,s, 2022)
(3Ef JfGhdg aj gPG GdcJGH ddcJGHI GdYdGLjI eONd ddGSJTaGA GdfaSj WQM jSJMb GdJCed hjecf ddbGQjA Cf jUd ef NdGdg Edi CfTWI cJGHjI JSGYO aj JQbjI PGJg, hJfejI SeGJg hYdGL LhGfH GdVYa aj TNUjJg(B. (3hJNUjU GdcJGH GdaUd Yf GdcJGHI GdCcGOjejI jLO ajg GdbGQjA GdHGMK eG jYjfg Ydi age efJLGJgG, hEfJGL CYeGdgG ef NWW HMKjI hCOhGJ hJbGQjQ hhSGFd YdejI(B. (3hGdcJGH jQcR Ydi YedjGJ HYjfgG efgG eG jJUd HYedjI GdeQGLYI, hgj ef Cge YedjGJ GdcJGHI ; MjK jchf dQUO GdCNWGA heYGdLJgG hddJZPjI GdQGLYI hCSGdjH GdOYe GddZhj CaVd GdCKQ aj JLhjO GdcJGHI hLhOI efJLGJgG ; hbO LGA GdcJGH aj NeSI aUhd jJfGhd ChdgG GdcJGHI GdYdGLjI hCfeGWgG hSjGbGJgG YHQ ehGbY GdJhGUd GdGLJeGYj, hLGA GdaUd GdKGfj djTNU GdCNWGA GdTGFYI aj cJGHGJ GdCaQGO ef efXhQ dZhi JQHhj, eegOG GdaUd jdjg NUU ddJZPjI GdQGLYI hCSGdjH GdOYe GddZhj dYdGL GdCNWGA(B. (3Ke LGA GdaUd GdQGHY djJfGhd feWG dG jecf GdGSJZfGA Yfg ; hgh GdcJGHI GdCcGOjejI ef MjK egGQGJgG hSjGbGJgG GdJOQjSjI(B. (3hGfJgi GdcJGH HaUd jOYe GdcJGHI aj hQT GdYed GdaQOjI hGdLeGYjI MjK GdGfJbGd ef GdaQOjI aj GdcJGHI Edi GdLeGYjI aj eeGQSI gPg GdegGQI GddZhjI(B. (3Efg cJGH jSYi Hcd LO Edi GdJQcjR Ydi GdcJGHI HhUagG fTGWG dZhjG ef efXhQ JQHhj dZhj faSj GLJeGYj jeKd eONdG ddGfJbGd ef GdGSJTaGA HGddZI Edi TaGA GddZI(B.s
(3JGQjN GdfTQ ef GdEjOGY(B.s
(3HHdjhLQGajI (B: (3UaMI (B121-134.s
Keywords: (3GdYdGL GdfaSjs -- (3GdYdGL GdSdhcjs -- (3GdYdGL GdEOQGcjs -- (3JYOjd GdSdhcs